Study on the processing outcomes of the atomic force microscopy tip-based nanoscratching on GaAs. (October 2021) - Wang, Jiqiang; Yan, Yongda; Jia, Bosen; Geng, Yanquan
Abstract: Nanostructures on GaAs have drawn significant attention because of their applications in photodetectors, photoemitter devices and emerging quantum devices. However, how to machine nanostructures with a desirable machined depth on GaAs is still a challenge. Atomic force microscopy (AFM) tip-based nanoscratching technique has been proven as a useful method to machine nanostructures. In this study, an AFM tip-based nanoscratching approach was used to machine nanochannels on GaAs. To predict the machined depth, a theoretical model was established during the removal of material in ductile regime. Furthermore, the influence of the machined depth on the material removal mechanism and the subsurface damage were also studied. The results demonstrated that materials were removed by ploughing and cutting respectively for the two sides of the channel when the machined depth was smaller than 11 nm. However, if the machined depth is larger than 11 nm, the removal of material for both sides of the channel was dominated by cutting. Transmission electron microscope analysis revealed the plasticity of the sample induced by nanoscratching was caused by stacking faults and dislocations, accompanied with nanocrystallization and amorphization. Our findings are of huge significance for understanding the material removal mechanism of GaAs at a nanometric machined depth. Graphical abstract: Unlabelled Image Highlights: A theoretical model for predicting machined depth was established. The effect of machined depth on the material removal state was investigated. The ductile material removal mechanism of GaAs during nanoscratching was revealed by TEM.